Effect of Addition of Soybean Oil to Feed on Eggs Hatching of Dumbo Catfish (Clarias gariepinus) - Saleh, Ratriana Hartini; Julyantoro, Pande Gde Sasmita; Pebriani, Dewa Ayu Angga (Advances in Tropical Biodiversity and Environmental Sciences; Vol 7 No 1 (2023): ATBES, 2023)
Many freshwater fish farming activities are carried out to meet the increasing demand for fish consumption. One commodity with high market demand is African catfish ( Clarias gariepinus ). The success of cultivation activities is the maintenance of broodstock is very influential on the eggs production. It is necessary to pay attention to the nutrients in the feed during cultivation. This study aims to determine the effect of adding soybean oil to feed on hatching eggs carried out at the Regional Technical Implementation Unit (UPTD) of Freshwater Aquaculture, Denpasar City. African catfish (C. gariepinus) were fed twice a day with feed mixed with soybean oil with three treatments namely 0%, 3% and 5% for five months. The fecundity and hatchability of eggs were calculated using a 10x10cm transect and analyzed using ANOVA analysis. Water quality observations were carried out once a week and ammonia at the end of each month. The results of this study obtained that fecundity values ranged from 214-546 grains/transect and egg hatchability values ranged from 0-62,62%. The results of observations of water quality showed a value that could still be tolerated by African catfish during the study. These results indicate that adding of 3% soybean oil to the broodstock feed of African catfish helps to increase the quality and quantity of hatching eggs.